(untitled) (Global Journal of Science Frontier Research, 2021)
The study assessed the quality of sources of drinking water used by scavengers in Gosa Area of the FCT. The study adopted the experimental research design. The study adopted the purposive sampling technique. Similarly, Sample used in the study were three sources of drinking water in the study area, namely from boreholes and shallow wells. Water samples collected was prevented from being exposed to sunlight. Samples were packed in plastic cooler containing ice for preservation and analysed within 24hours from the time of sample collection to avoid errors that may be introduced due to environmental factors. The samples collected were comparatively analyzed based on their physical and chemical properties, within the premise of drinking water quality as approved by the Standard Organisation of Nigeria (SON), the National Agency for Food, Drug Administrative Control (NAFDACT). The results of the study revealed that all the sampled water sourced in the study were odourless and in line with the requirement of NAFDAC and SON.